Penentuan Lokasi Stasiun Pengisian Kendaraan Listrik Umum (SPKLU) di Kota Mojokerto Menggunakan Metode Mixed-Integer Linear Programming (MILP) - Nugraha, Christian Cahya; Herlina, Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to determine the optimal location of Electric Vehicle Public Charging Stations (SPKLU) in Mojokerto City using the Mixed-Integer Linear Programming (MILP) method. The research is motivated by the increasing number of electric vehicles in Mojokerto, which is not yet supported by adequate charging infrastructure. The data used include the distribution of EV users, potential charging station locations, distance matrices, service capacity, and construction cost estimates. The MILP model is formulated to minimize the total construction and operational costs while maximizing service coverage. The results identify three strategic optimal locations based on proximity to demand clusters and cost efficiency. The findings provide practical recommendations for local governments and PLN to develop sustainable EV charging infrastructure in Mojokerto City.